A two-step geospace storm as a new tool of opportunity for experimentally estimating the threshold condition for the formation of a substorm current wedge - L. F. Chernogor (Annales Geophysicae)
In the study of coupling processes acting within the upper atmosphere, a major challenge remains in quantifying the transformation of energy. One of the energy pathways between the ionospheric heights and the magnetosphere is the diversion of the cross-tail electric current into the ionosphere through the current wedge. One of the most interesting observations made in this study shows that during one of the two steps of the two-step storm, part of the near-Earth cross-tail current closed itself via the ionosphere, to which it was linked by the substorm current wedge, and manifested itself in the magnetograms acquired at equatorial and high-latitude stations on the night side of the Earth. As result, the two-step character of this storm has allowed us to suggest that the Bz interplanetary magnetic field component threshold for the formation of the substorm current wedge lies within the −(22–30) nT interval. Consequently, this study suggests, for the first time, that the emergence of a current wedge during a two-step geospace storm may be quantified by a threshold value of the interplanetary magnetic field (IMF) Bz component utilizing observations made during a two-step geospace storm with ground-based magnetometers. The study, for the first time, convincingly attests to the two-step geospace storm to be the best possible solar–terrestrial event of opportunity for realizing a technique for estimating the IMF Bz component threshold for the formation of the substorm current wedge. These conclusions have been drawn from the examination of the latitudinal dependence of variations in the geomagnetic field on the surface of the Earth on the global scale during the severe two-step geomagnetic storm of 23–24 April 2023, a major two-step storm in solar cycle 25. The data available via the INTERMAGNET magnetometer network (https://imag-data.bgs.ac.uk/GIN_V1/GINForms2, last access: 19 December 2024) were chosen for two near-meridional chains of stations, one in the Western (eight stations) and the other in the Eastern (10 stations) Hemisphere, which were situated, for the first time, in such a way that one of them was in the night hemisphere during both of the two steps of the geomagnetic storm. Other features of this two-step storm include the following. In the Western Hemisphere, the fluctuations in the geomagnetic field strength on the days used as a quiet-time reference period usually did not exceed a few tens of nanoteslas (nT), whereas in the course of the disturbed days, the variations in the geomagnetic field strength increased by a factor of 2 to 10 and reached a few hundred nanoteslas. In the Eastern Hemisphere during quiet times, the middle- and low-latitude magnetometer stations generally recorded strength fluctuations smaller than 10–20 nT, while during the disturbed period, the fluctuations increased by a factor of 2–5 and greater, attaining ± (50–70) nT. The strength fluctuations showed a considerable increase of up to 300–700 nT at high latitudes. The northward component of the geomagnetic field, X, exhibited the greatest perturbations at all latitudes in both hemispheres as the level of strength fluctuations decreased with decreasing latitude. The geomagnetic field strength fluctuations recorded at the magnetometer stations nearly equidistant from the Equator were observed to be close in magnitude. The strength fluctuations observed with the stations at close latitudes but in different hemispheres were also close in value.